Impact on clinical outcomes of right ventricular response to percutaneous correction of secondary mitral regurgitation. (6th August 2021) - Caiffa, Thomas; De Luca, Antonio; Biagini, Elena; Lupi, Laura; Bedogni, Francesco; Castrichini, Matteo; Compagnone, Miriam; Tusa, Maurizio; Berardini, Alessandra; Merlo, Marco; Fabris, Enrico; Popolo Rubbio, Antonio; et al.
Abstract: Aims: In patients with heart failure and reduced ejection fraction (HFrEF) and secondary mitral regurgitation (SMR), impaired right ventricular function (RVF) may negatively influence the prognosis. Percutaneous mitral valve repair (pMVR) can promote the recovery of RVF. We sought to characterize the response of the right ventricle to pMVR in HFrEF with SMR and to assess the association between improved RVF after pMVR and outcomes. Methods and results: Overall, 221 patients with HFrEF and SMR ≥3+ successfully treated with pMVR in four tertiary care centres for heart failure were included. Improved RVF was defined as Δ right ventricular fractional area change (ΔRVFAC) ≥5% at early follow‐up (median time 4 months). The primary endpoint was a composite of death/heart transplantation (D/HT). Mean age was 69 ± 11 years, mean left ventricular ejection fraction was 31 ± 8% and mean RVFAC was 34 ± 9%. ΔRVFAC ≥5% occurred in 88 patients (40%) and was independent of the measures of left ventricular reverse remodelling. During a median follow‐up of 29 months (interquartile range 12–46), 81 patients (37%) reached the primary endpoint. After adjustment for other significant covariates, ΔRVFAC ≥5% was significantly associated with lower risk of D/HT (hazard ratio 0.52, 95% confidence interval 0.29–0.94, P  = 0.030). In the secondary outcome analysis exploring the risk of heart failure hospitalizations, ΔRVFAC ≥5% confirmed the prognostic association with the endpoint. Conclusions: In patients with HFrEF and SMR, about 40% of patients improved RVF after pMVR. RVF improvement was associated with better long‐term survival free from HT and lower risk of heart failure hospitalization. Abstract : In a cohort of 221patients with heart failure with reduced ejection fraction and secondary mitral regurgitation, the early improvement of right ventricular function after percutaneous mitral valve repair was associated with lower risk of the composite study endpoint (death/heart transplantation). This result was independent of measures of left ventricular reverse remodelling. D/HT, death/heart transplantation; LVEF, left ventricular ejection fraction; LVRR, left ventricular reverse remodelling; pMVR, percutaneous mitral valve repair; RV, right ventricular; RVF, right ventricular function; RVFAC, right ventricular fractional area change.